Comprehensive Evaluation of Nutritional, Physicochemical, and Volatile Profiles of Selected Bovine Head Muscles - Qihan Liu; Anthony Pius Bassey; Ziyu Li; Guanghong Zhou; Xia Fan; Keping Ye (Foods)
This study analyzed the nutritional composition, physicochemical properties, and volatile profiles of three major bovine head muscles—medial pterygoid, masseter, and buccinator—to reduce byproduct resource waste and increase the utilization rate of bovine head to establish a foundation for its industrial use. Compared to tenderloin, which is popular among consumers, these head muscles were found to be rich in collagen (4.90–13.1 mg/g), low in fat (0.39–1.61%), and abundant in free amino acids (143.93–223.00 mg/100 g). Their compact fiber structures, with minimal gaps between myocytes, resulted in lower cooking and press losses, making them suitable for various production processes. Notably, the medial pterygoid and masseter muscles contained high levels of polyunsaturated fatty acids (PUFAs) and lower saturated fatty acids (SFAs), with a PUFA/SFA ratio exceeding 0.45. The buccinator muscle, while containing more volatile organic compounds associated with undesirable odors and bitter amino acids, was not indicative of spoilage. Overall, this study confirmed that bovine head muscles possess high collagen, low fat, and diverse nutritional qualities, making them suitable as premium raw materials for value-added meat products, and their returns will be most economically equal to the meat derived from cattle.